Crystal structure of (Z)-2-(1-benzyl-2-oxoindolin-3-ylidene)-N-phenylhydrazine-1-carbothioamide - G. Vimala (Acta Crystallographica Section E: Crystallographic Communications, 2015)
The title compound, C22H18N4OS, crystallized with four independent molecules (A, B, C and D) in the asymmetric unit. All four molecules have a Z conformation about the C=N bond with the benzyl ring being inclined to the indoline ring mean planes by 73.4 (2), 77.9 (2), 73.2 (2) and 77.2 (2)° in molecules A, B, C and D, respectively. In molecules A and B, the phenyl ring is inclined to the mean plane of the indoline ring mean plane by 12.0 (2) and 12.2 (2)°, respectively. However, in molecules C and D, the same dihedral angles are larger, viz. 37.3 (2) and 36.4 (2)°, respectively. Consequently, the benzyl and phenyl rings are almost normal to one another in molecules A and B [dihedral angles = 80.3 (3) and 87.1 (3)°, respectively], while in molecules C and D, the same dihedral angles are only 48.8 (2) and 43.8 (3)°, respectively. There is an intramolecular N—H...O hydrogen bond in each molecule with an S(6) ring motif. There are also short intramolecular N—H...N and C—H...S contacts in each molecule. In the crystal, molecules are linked via C—H...S hydrogen bonds and C—H...π interactions, forming a three-dimensional structure. The crystal was refined as a non-merohedral twin with a final BASF value of 0.110 (1).